Teucrium montanum L.-Unrecognized Source of Phenylethanoid Glycosides: Green Extraction Approach and Elucidation of Phenolic Compounds via NMR and UHPLC-HR MS/MS - Ana Mandura Jarić; Ana Čikoš; Marijana Pocrnić; Krunoslav Aladić; Stela Jokić; Danijela Šeremet; Aleksandra Vojvodić Cebin; Draženka Komes (MDPI AG, 2023)
Health-oriented preferences, a demand for innovative food concepts, and technological advances have greatly influenced changes in the food industry and led to remarkable development of the functional food market. Incorporating herbal extracts as a rich source of bioactive compounds (BC) could be an effective solution to meet the high demand of consumers in terms of expanding the high-quality range of functional foods. The aim of this study is the valorization of the bioactive potential of T. montanum L., an understudied Mediterranean plant species, and the in-depth elucidation of a polyphenolic profile with a UHPLC-HR MS/MS and NMR analysis. The total phenolic content (TPC) and antioxidant capacity (AC) were determined on heat-assisted (HAE), microwave-assisted (MAE) and subcritical water (SWE) extracts. In terms of antioxidant capacity, SWE extracts showed the most notable potential (ABTS: 0.402-0.547 mmol eq Trolox g−1 dw, DPPH: 0.336-0.427 mmol eq Trolox g−1 dw). 12 phenolic compounds were identified in the samples of T. montanum from six microlocations in Croatia, including nine phenylethanoid glycosides (PGs) with total yields of 30.36-68.06 mg g−1 dw and 25.88-58.88 mg g−1 dw in HAE and MAE extracts, respectively. Echinacoside, teupolioside, stachysoside A, and poliumoside were the most abundant compounds HAE and MAE extracts, making T. montanum an emerging source of PGs.